Qualitative and Quantitative Dosage of the Anti M-Type Phospholipase A2 Receptor Autoantibody: One-Year Experience in Quebec's Reference Center. (October 2021) - Leclerc, Simon; Benkirane, Karim; Nadeau-Fredette, Annie-Claire; Elftouh, Naoual; Lafrance, Jean-Philippe; Pichette, Vincent; Royal, Virginie; Lamarche, Caroline; Laurin, Louis-Philippe
Background: Quantification of the M-type phospholipase A2 receptor antibodies (anti-PLA2R) is now an essential tool for diagnosis and management of primary membranous nephropathy (MN). Since October 2018, Hôpital Maisonneuve-Rosemont (HMR) has been designated as Quebec's reference center for serum anti-PLA2R antibody testing by the Institut National d'Excellence en Santé et Services Sociaux (INESSS), the regulatory body on drugs and tests usage in Quebec. Objectives: To describe the 2-step method of serum qualitative and quantitative anti-PLA2R antibody testing during its first year of use in Quebec and analyze its diagnostic value in the province's population. Design: Retrospective cohort study. Setting: Single-center academic teaching hospital in Quebec, Canada. Patients: All patients who had a serum anti-PLA2R antibody test analyzed at HMR from October 1, 2018, to October 1, 2019, were included in the study. Measurements: Serum anti-PLA2R antibodies were screened by indirect immunofluorescence tests. If results were positive or undetermined, it was followed by a quantitative enzyme-linked immunosorbent assay (ELISA) test. Both tests were based on a commercial kit developed by the same company. Methods: We calculated sensitivity, specificity, predictive value, and likelihood ratio for both tests, using kidney biopsy findings performed at HMR as the gold standard. Results: In Quebec, a total of 1690 tests were performed among 1025 patients during the study year. A small proportion of these patients (8%) were followed at HMR. Patients tested at HMR and in the rest of Quebec had similar characteristics. Test validity was only characterized for patients tested at HMR. Sensitivity and specificity were, respectively, 58% and 100% for the qualitative test, and 71% and 100% for the quantitative test. The combined net sensitivity was 42% and the net specificity 100%. The net positive and negative predictive value were 100% and 84% respectively, whereas the net negative likelihood ratio was 0.58. Limitations: As the detailed analysis was only possible in the small proportion of patients clinically followed at HMR, there is a possible selection bias. Another potential selection bias was the focus on patients who were selected to have a kidney biopsy, probably because of more severe disease, higher probability of glomerulonephritis, or lesser number of comorbidities. Given the retrospective nature of this study, there was no systematic kidney biopsy or serum PLA2R antibody testing performed. Finally, we were unable to provide detailed information on the timing between immunosuppressive therapy and anti-PLA2R results. Conclusions: Serum anti-PLA2R antibody testing was widely used in Quebec during its first year of availability. A 2-step approach, using a qualitative test first, followed by a quantitative test if the results are positive or undetermined, appears efficient to avoid useless quantitative testing in negative patients and to better characterize undetermined results on immunofluorescence. Trial registration: Due to the retrospective nature of this study, no trial registration was performed.